2018
DOI: 10.14687/jhs.v15i4.5501
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between self-efficacy and life satisfaction according to exercise participation in obese female university students

Abstract: The aim of this study was to examine the relationship between self-efficacy and life satisfaction according to exercise participation in obese female university students. The sample of the study consisted of over 18 age 145 obese (BMI≥30) that were regularly exercising for at least 4 days, 90 minutes in a week for 6 mounts and 136 obese sedentary (BMI≥30). The mean age was (20.69 ± 1.84) for obese female students who participated regular exercise and (20.19 ± 1.49) for obese female university students who was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…It is thought that the meaning they attribute to the motivational climate in a sports environment where young basketball players and older basketball players are together is not affected by the ages of the athletes. 39 Our findings are also in line with other studies linking the development of motivational climate with mental toughness 46,47,48,49,50,51,52,53,54,55,56,57,58,59,60…”
Section: Discussionsupporting
confidence: 86%
“…It is thought that the meaning they attribute to the motivational climate in a sports environment where young basketball players and older basketball players are together is not affected by the ages of the athletes. 39 Our findings are also in line with other studies linking the development of motivational climate with mental toughness 46,47,48,49,50,51,52,53,54,55,56,57,58,59,60…”
Section: Discussionsupporting
confidence: 86%
“…Regarding academic self-efficacy, this variable is positively related to psychological well-being, confirming the studies of Burger and Samuel (2017) and Toros et al (2018), who concluded that self-efficacy was associated with psychological well-being. Moreover, academic self-efficacy showed a negative relationship with test anxiety and a positive relationship with academic performance (Bandura, 1994(Bandura, , 1997Roick & Ringeisen, 2017).…”
Section: Discussionsupporting
confidence: 84%
“…In addition, autonomous motivation showed an indirect effect on reducing test anxiety. Even though there is empirical evidence of the benefits of autonomous motivation on academic self-efficacy (Wang et al, 2016) and of the latter on academic performance (Honicke & Broadbent, 2016) and life satisfaction (Antaramian, 2017;Burger & Samuel, 2017;Toros et al, 2018), this finding shows the mediation of academic self-efficacy between autonomous motivation and academic performance in pre-university students, who -while aware of their low academic level (Outes-León et al, 2020)  require their autonomous motivation to be encouraged for developing self-efficacy to improve their performance and psychological well-being (life satisfaction).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Our findings are also in line with other studies linking the development of motivational climate with mental toughness. 22,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42…”
Section: Discussionmentioning
confidence: 99%